Did rapid smallholder-led agricultural growth fail to reduce rural poverty?: Making sense of Malawi’s poverty puzzle - Pauw, Karl; Beck, Ulrik; Mussa, Richard (United Nations University, 2014)
Disappointment was widespread when rapid economic growth since 2005, coupled with a smallholder-targeted fertilizer subsidy program, failed to significantly reduce poverty in Malawi. Official estimates for 2011 showed a 1.7 percentage point decline in national poverty between 2005 and 2011, while rural poverty increased marginally. In this study we estimate an alternative set of regional poverty lines using a cost of basic needs method that allows the consumption bundle to vary spatially and temporally while ensuring utility consistency. Our poverty figures suggest a substantial 7.3 percentage point decrease in national poverty over the analysis period, driven largely by a sharp reduction in rural poverty. These results are more consistent with the observed level of economic growth and improvements in several non-monetary dimensions of well-being. However, we find that extreme poverty did increase, suggesting that the most vulnerable people continue to be excluded from the benefits of economic policy and growth.